Serological Surveillance of Influenza D Virus in Ruminants and Swine in West and East Africa, 2017–2020 - (:unkn) unknown (My University, 2021)
This study was approved by the St. Jude Children’s Research Hospital Institutional Animal Care and Use Committee (Amended IACUC Approval # 546-100491-07/17; expires 4/5/23). This study was approved by the St. Jude Children’s Research Hospital Institutional Animal Care and Use Committee (Amended IACUC Approval # 546-100491-07/17; expires 4/5/23).
Keywords: African Research